2011
DOI: 10.1111/j.1444-0938.2010.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Applications of the multifocal electroretinogram in the detection of glaucoma

Abstract: Glaucoma is one of the most important eye diseases resulting in blindness worldwide. It affects the inner retina and is without signs and symptoms in the early stages, making early detection of glaucoma important for eye care professionals. Electroretinography (ERG) is an objective technique used to measure retinal electrical responses, which directly reflect retinal function. The multifocal electroretinogram (mfERG) is a relatively new tool in this area. Various modifications of the mfERG stimulation paradigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 92 publications
(164 reference statements)
0
21
0
1
Order By: Relevance
“…This non-linear component is believed to be generated predominantly from the inner retina 10. It may be used as an indicator of inner retinal dysfunction due to glaucoma,11 12 and its compromise shows that the fast-adaptive mechanisms from the retina are affected in inner retinal disease 13…”
Section: Introductionmentioning
confidence: 99%
“…This non-linear component is believed to be generated predominantly from the inner retina 10. It may be used as an indicator of inner retinal dysfunction due to glaucoma,11 12 and its compromise shows that the fast-adaptive mechanisms from the retina are affected in inner retinal disease 13…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] A kernel analysis applied to mfERG responses can be used to assess nonlinear functions of the visual system. 25 Since the first-order kernel of mfERG originates primarily in the preganglionic elements (photoreceptors and bipolar cells), 26 and several studies have reported altered mfERG in OAG and in ocular hypertension, [27][28][29][30][31][32] the present authors believed it would be interesting to clarify whether a dysfunction of the preganglionic elements may occur in OAG.…”
mentioning
confidence: 99%
“…The ‘kernel analysis’ was particularly useful to assess that in glaucoma, a not exclusive dysfunction of the GCs and their fibres (mainly detected by PERG recordings, see Wilsey & Fortune as a review) was present, but that a functional impairment of the preganglionic elements may also occurs (Chan & Brown ; Chan ; Chan et al. ; Parisi et al. ).…”
Section: Introductionmentioning
confidence: 99%